The adventures of climate science in the sweet land of idle arguments. (May 2016) - Winsberg, Eric; Goodwin, William Mark
Abstract: In a recent series of papers Roman Frigg, Leonard Smith, and several coauthors have developed a general epistemological argument designed to cast doubt on the capacity of a broad range of mathematical models to generate "decision relevant predictions." The presumptive targets of their argument are at least some of the modeling projects undertaken in contemporary climate science. In this paper, we trace and contrast two very different readings of the scope of their argument. We do this by considering the very different implications for climate science that these interpretations would have. Then, we lay out the structure of their argument—an argument by analogy—with an eye to identifying points at which certain epistemically significant distinctions might limit the force of the analogy. Finally, some of these epistemically significant distinctions are introduced and defended as relevant to a great many of the predictive mathematical modeling projects employed in contemporary climate science. Highlights: We discuss the claims of Frigg et al. concering nonlinear models. They claim that such models are maladapted to producing decision relevant predictions. We trace and contrast two very different readings of the scope of their argument. We argue that most of their claims are overstated.